Relationship Between Gender and Entrepreneurship of Small and Medium-Sized Companies in Mexico - Chávez-Márquez, Irma Leticia; Morale, Carmen Romelia Flores; Sánchez-Acosta, Luis Raúl; Parada, Ana Isabel Ordóñez (European Scientific Journal, ESJ, 2018)
This paper focuses on determining the relationship between gender and the entrepreneurship of small and medium-sized companies in Mexico. The research was quantitative, and it uses the database of the National Institute of Statistics and Geography. The analysis was conducted during the period from October 2017 to February 2018. The variables considered were: independent variable such as gender; dependent variables, entrepreneurship by economy sector (manufacturing, commerce and private non-financial services); and control variables, hourly income and average schooling. Descriptive statistics, linear regression models, analysis of variance, and Pearson correlation coefficients were obtained. The main results indicate that there are differences related to gender which is based on the type of small and medium companies undertaken by economy sector in Mexico. Women undertake more in the trade sector, while men also undertake more in the manufacturing sector. Based on the female gender where lower average schooling is, there is a greater entrepreneurship of small and medium-sized companies. On the other hand, considering the male gender where higher average schooling is, there is more entrepreneurship in the commerce sector. The variation in the entrepreneurship of small and medium-sized companies is 43% higher than in the female gender. Also, in both genders, the higher the schooling is, the higher would be the income.